Structure and Dynamics of Dinucleosomes Assessed by Atomic Force Microscopy. (21st August 2011) - Filenko, Nina A.; Palets, Dmytro B.; Lyubchenko, Yuri L.
Abstract : Dynamics of nucleosomes and their interactions are important for understanding the mechanism of chromatin assembly. Internucleosomal interaction is required for the formation of higher-order chromatin structures. Although H1 histone is critically involved in the process of chromatin assembly, direct internucleosomal interactions contribute to this process as well. To characterize the interactions of nucleosomes within the nucleosome array, we designed a dinucleosome and performed direct AFM imaging. The analysis of the AFM data showed dinucleosomes are very dynamic systems, enabling the nucleosomes to move in a broad range along the DNA template. Di-nucleosomes in close proximity were observed, but their population was low. The use of the zwitterionic detergent, CHAPS, increased the dynamic range of the di-nucleosome, facilitating the formation of tight di-nucleosomes. The role of CHAPS and similar natural products in chromatin structure and dynamics is also discussed.